Evaluation of planarization performance for a novel alkaline copper slurry under a low abrasive concentration - 蒋勐婷 刘玉岭 袁浩博 陈国栋 刘伟娟 (Journal of semiconductors, 2014)
A novel alkaline copper slurry that possesses a relatively high planarization performance is investigated under a low abrasive concentration. Based on the action mechanism of CMP, the feasibility of using one type of slurry in copper bulk elimination process and residual copper elimination process, with different process parameters, was analyzed. In addition, we investigated the regular change of abrasive concentration effect on cop- per and tantalum removal rate and within wafer non-uniformity （WIWNU） in CMP process. When the abrasive concentration is 3 wt%, in bulk elimination process, the copper removal rate achieves 6125 ~/min, while WIWNU is 3.5%, simultaneously. In residual copper elimination process, the copper removal rate is approximately 2700 A/min, while WIWNU is 2.8%. Nevertheless, the tantalum removal rate is 0 A./min, which indicates that barrier layer isn＇t elinainated in residual copper elimination process. The planarization experimental results show that an excellent planarization performance is obtained with a relatively high copper removal rate in bulk elimination process. Meanwhile, atier residual copper elimination process, the dishing value increased inconspicuously, in a control- lable range, and the wafer surface roughness is only 0.326 nm （sq 〈 1 nm） alter polishing. By comparison, the planarization performance and surface quality of alkaline slurry show almost no major differences with two kinds of commercial acid slurries after polishing. All experimental results are conducive to research and improvement of alkaline slurry in the future.